Wisata Halal Dan Komodifikasi Agama - Muhamad Taufik; Irfan Goffary (ISLAMICA, 2020)
Halal tourism was originally an attempt by the Islamic world to preserve its cultural heritage, while at the same time providing reinforcement to the Islamic world, both in the economic aspect, as well as the communal emotions of its adherents. However, in its aftermath, this halal tourism moves to be a label that is processed in such a way for business purposes only. There is a process of commodification of religion that makes halal labels no longer fit their use value, but rather is considered at how large the exchange rate is.